1981
DOI: 10.1097/00006842-198106000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Denial in Dialysis Patients: Relationship to Compliance and Other Variables

Abstract: Denial has been documented as an important defense mechanism to helping the chronically ill cope with their disease. With respect to a dialysis population, however, the role of denial has been ambiguous. The purpose of this study were 1) to examine the physiological and psychological correlates of denial in a dialysis population and 2)( to examine the relationship between use of denial and compliance to fluid restrictions. Subjects were 46 self- and limited-care dialysis patients. From this subject pool two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The latter refers to the observation that some patients cannot tolerate open dependency on other individuals or on the HD machine and may behave in a manner inju rious to their own health as a result. It is unclear whether denial is related to noncompliance [32,33].…”
Section: Determinants For Compliance In Esrd Patientsfactors Related mentioning
confidence: 99%
“…The latter refers to the observation that some patients cannot tolerate open dependency on other individuals or on the HD machine and may behave in a manner inju rious to their own health as a result. It is unclear whether denial is related to noncompliance [32,33].…”
Section: Determinants For Compliance In Esrd Patientsfactors Related mentioning
confidence: 99%
“…For this purpose, it is more helpful to investi gate beliefs and attitudes patients may hold which might be associated with poor adherence. Such cognitive factors investigated to date include locus of control [7][8][9][10][11][12][13][14], health beliefs [8. 15.…”
Section: Introductionmentioning
confidence: 99%
“…15. 16], causal attributions [13], and more spe cific cognitive variables such as resourcefulness [17] or denial [7],…”
Section: Introductionmentioning
confidence: 99%
“…Under a severely stressful condition, such as dialysis therapy [16] and organ transplantation [17], 'denial' is an effective psychological mechanism for coping to prevent depression and allow satisfactory adaptation to maintenance dialysis treatment. Alexithymia is charac terized by difficulty in expressing one's feelings verbally and a lack of fantasy [7][8][9][10][11][12], Many studies have shown that alexithymia results from a variety of psychological sources which are associated with defense mechanisms such as 'denial' [8,9,19].…”
Section: Discussionmentioning
confidence: 99%